Genetic evidence reveals a causal relationship between rheumatoid arthritis and interstitial lung disease - Zhao, Rong; Zhang, Yi-Wen; Guo, Jin-Cheng; Qiao, Jun; Song, Shan; Zhang, Ting-Ting; Zhang, He-Yi; Zhang, Sheng-Xiao (Frontiers in Genetics, 2024)
Background/Purpose: Previous epidemiological studies have associated interstitial lung disease (ILD) with rheumatoid arthritis (RA), yet the causality of this relationship remains uncertain. This study aimed to investigate the genetic causal link between ILD and RA. Methods: Genome-wide association studies (GWAS) statistics for the ILD and RA were collected from public datasets. Relevant single nucleotide polymorphisms (SNPs) were selected by executing quality control steps from the GWAS summary results. A two-sample bi-directional Mendelian randomization (MR) analysis was performed to assess the causal relationship between the two conditions. The MR analysis primarily utilized the Inverse Variance Weighted (IVW), Weighted Median (WM), and MR-Egger regression methods. Sensitivity analyses, including MR-Egger, leave-one-out, and MR Pleiotropy Residual Sum and Outlier (MR-PRESSO), were conducted to evaluate heterogeneity and pleiotropy. Replication analyses using Asian datasets were also conducted to enhance the robustness of our findings. Results: In the European population, RA was found to increase the risk of ILD by 9.6% (OR: 1.096, 95%CI: 1.023-1.174, P = 0.009). Conversely, ILD was associated with a 12.8% increased risk of RA (OR: 1.128, 95%CI: 1.013-1.256, P = 0.029). Replication analyses from Asian GWAS studies further supported these findings, particularly the increased risk of ILD attributable to RA (OR: 1.33, 95% CI: 1.18-1.49, P-value < 0.001). Conclusion: Our findings underscore the clinical importance of screening for ILD in RA patients and suggest that effective management of RA could significantly benefit ILD patients. The potential applicability of novel RA treatments to ILD warrants further exploration. Additionally, racial disparities in the manifestation of these diseases should not be overlooked, as they may offer new perspectives for targeted therapies in diverse populations.